(untitled) (Research, Society and Development, 2022)
Ocular myopia is one of the major disorders that commonly affect the young population, mediated by stimulating factors that determine this problem, such as the use of screens and less exposure to outdoors. Given the COVID-19 pandemic, arrangements such as the use of electronic equipment, remote classes, virtual meetings and the reinforcement of social isolation, became potential for the more frequent development of this issue. This article aims to highlight the possible association between myopia and electronics exposure in view of the pandemic perspective. This is a systematic literature review, descriptive-discursive, carried out from scientific databases to carry out the study, such as Scielo, Pubmed, Lilacs, Science Direct and Academic Google. To search for articles, the English terms “myopia”, “myopia and screen exposure”, “myopia in children”, “myopia in children and adolescents and screen exposure” and “myopia and pandemic” and their corresponding terms in Portuguese were used. Among the studies analyzed, one of its results showed that the prevalence of myopia is three times higher in 6 years old children, twice as high for 7 years old children and 1.4 for 8 years old children. 9 to 13 years old children were not affected, despite being exposed to a longer screen time, which may show that younger children have a greater potential to acquire myopia caused by electronics. Another article, moreover, claimed that prolonged use of screens causes a decline in vision of exposed children. The study allowed us to identify that the emission of blue violet light by screens is likely to cause possible future damage to vision, as well as low exposure to the environment, which demonstrates a greater need for educational guidelines and public policies in order to alleviate the situation addressed.